Antigen-Specific Polyclonal Cytotoxic T Lymphocytes Induced by Fusions of Dendritic Cells and Tumor Cells. (7th April 2010) - Koido, Shigeo; Homma, Sadamu; Hara, Eiichi; Namiki, Yoshihisa; Ohkusa, Toshifumi; Gong, Jianlin; Tajiri, Hisao
Abstract : The aim of cancer vaccines is induction of tumor-specific cytotoxic T lymphocytes (CTLs) that can reduce the tumor mass. Dendritic cells (DCs) are potent antigen-presenting cells and play a central role in the initiation and regulation of primary immune responses. Thus, DCs-based vaccination represents a potentially powerful strategy for induction of antigen-specific CTLs. Fusions of DCs and whole tumor cells represent an alternative approach to deliver, process, and subsequently present a broad spectrum of antigens, including those known and unidentified, in the context of costimulatory molecules. Once DCs/tumor fusions have been infused back into patient, they migrate to secondary lymphoid organs, where the generation of antigen-specific polyclonal CTL responses occurs. We will discuss perspectives for future development of DCs/tumor fusions for CTL induction.